Narrative Structure and Dystopian Elements in P.D. James’s Children of Men - Davu, Syeh Nathaniel Ahmad (English Literature Study Program, 2024)
The term of genres refers to the particular texts that have the similarity of meaning and gives particular identity/meaning to the texts. While the term of genres is used to classify the particular texts that have the same meaning, the narrative structure theory argues that there is a meaning behind the structure of the texts. Dystopia is a kind of genres in fiction which refers to particular texts that have the meaning about a fictious world that is filled with oppressive society. One example of literary works that represents the dystopian sub-genre characteristics is the Children of Men novel by P.D. James. This research aims to analyze the way in which the narrative structure is formed in James’s the Children of Men novel, by the use of narrative structure theory by Tzvetan Todorov, and the way in which the narrative structure represents the dystopian sub-genre characteristics by the use of Terri Chung’s dystopian characteristics theory. The results of this research show that the novel contains all of five narrative stages, and the process of changing narrative stages are absolutely influenced by the changes that happens in Theo’s life. In addition, this research also finds that the narrative structure and the dystopian characteristics of the novel are interconnected, since each dystopian characteristic has its own role to deliver the meaning behind each narrative stage in the novel. Based on the scope and limitation of this research, the researcher only focused on the intrinsic aspects of the novel. So, there will be many research that can be conducted by using this novel as material object, since there are still many theories and approaches that can be used to do the literary criticism for this novel.